Rings, Modules and Codes - Leroy, André (Contemporary Mathematics Ser., 2019)
This book contains the proceedings of the Fifth International Conference on Noncommutative Rings and their Applications, held from June 12-15, 2017, at the University of Artois, Lens, France. The papers are related to noncommutative rings, covering topics such as: ring theory, with both the elementwise and more structural approaches developed; module theory with popular topics such as automorphism invariance, almost injectivity, ADS, and extending modules; and coding theory, both the theoretical aspects such as the extension theorem and the more applied ones such as Construction A or Reed-Mull.